DETERMINAN KOMUNIKASI TERHADAP KINERJA APARATUR SIPIL NEGARA PADA PUSKESMAS MERDEKA KECAMATAN MERDEKA KABUPATEN KARO - Jupianus Sitepu (Universitas Quality, 2021)
This research aims to analyse how much communication to the performance of employees of the village Health center of Merdeka District of Merdeka Karo District. The samples in this study were 31 employees of the village health Puskesmas Merdeka Sub District Merdeka District, and then conducted an analysis of data by using data analysis covering the validity test, reliability test, test normality, heteroskedastisity test, t test, test Determination (R2). The data has fulfilled the validity test, the realibility test and the processed heteroskedastisity test resulting in the following simple liner regression equations: Y= 22.86 + 0.478 X + e. Nilai ???? ℎi????????????g > t tabel is a communication variable of 3,832, the hypothesis of using T test indicates that the free X variable is partially proven to have a significant effect on the Y bound variable that is the test T obtained ???? ℎi????????????g > t tabel or 3,832 > 1.699. The Adjusted R Square number of 0336 indicates that 33.6% of the bound variable (Y) can be described by the free variable (X).